Evaluating a magnetic resonance imaging of the third-trimester abdominal pregnancy: What the radiologist needs to know. Issue 48 (December 2017) - Deng, Mei-xiang; Zou, Yu
Abstract: Introduction: A 33-week abdominal pregnancy is an extremely rare type of ectopic pregnancy that is potentially life-threatening for the mother and fetus. Reports of using magnetic resonance imaging (MRI) in the third-trimester abdominal pregnancy are very few. Patient concerns: A 24-year-old woman (gravida 2, para 1, living 0) at 33 weeks' gestation presented to local hospital complaining of vaginal bleeding for 2 months and lower abdominal pain for 2 days. Then, the woman was transferred to our hospital for suspected abdominal pregnancy, which was confirmed at our hospital on ultrasonography and further evaluated in detail on MRI. Diagnoses: The woman was diagnosed as having abdominal pregnancy. Interventions: The woman was managed surgically, the unviable fetus was removed, and the placenta was left in situ. Then, the woman was managed with fluids, blood transfusion, antibiotics, and systemic methotrexate after surgery. Outcomes: At 42 days postoperatively, the affected woman was discharged in a good condition. Conclusions: By using MRI, we can accurately diagnose an abdominal pregnancy. MRI provides more details than ultrasonography, and explains the possible mechanism of abdominal pregnancy. We advocate using MRI to help surgical planning and improve outcome in cases of abdominal pregnancy.